Siliconizing process of mild steel substrate by using Tronoh Silica Sand (TSS): An experimental investigation - Othman, M. (Elsevier B.V., 2015)
Siliconizing is one of the surface hardening treatments where silica diffuses into a metal substrate forming a thin layer coating material. This paper discussed on appropriate Design of Experiment (DOE) involved in performing siliconizing process onto mild steel substrate using Tronoh Silica Sand (TSS). Available knowledge on the siliconizing related parameters, material selection issue, temperature-time dependence and effects on the interface, structure and properties of siliconized substrate were critically reviewed. Critical parameters for the siliconizing process on mild steel substrate by using TSS were established. In order to enhance formation of the thin film coating, simultaneous TSS powder pack for siliconizing process was designed. Associated siliconizing mechanism in producing the thin film coating will be discussed and established. Â© 2015 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license.